2011
DOI: 10.7498/aps.60.066403
|View full text |Cite
|
Sign up to set email alerts
|

Effect of far field flow on the stability of thespherical crystal in undercooled melt

Abstract: A model is developed to investigate the effects of far field flow on the solidification of a spherical particle from the melt, under the influence of thermal and solute flow. The stability of the spherical interface is studied and the growth rate of the interface perturbation is calculated. The perturbation to the maximum growth rate becomes larger when the spherical radius increases. The downwind side of the interface is more unstable than the upwind side. The effect of far field flow reduces the critical rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…[7] Though various experimental observations and numerical simulations explicitly suggest the significant effect of the convection on the interface microstructure formation, theoretical investigations of the morphological evolution of interface during crystallization in the stirred melt and solution are still very limited due to the complicated effects of convection. [2,[8][9][10][11][12][13][14][15][16][17] Hence, there is a strong need for the common analytical method to predict the experimentally observed particle morphologies developed under different flow conditions. A feasible way is to model the growth of spherical particles in the complex flow of the stirred liquid as a singularly perturbed free boundary problem and find its asymptotic solution by using the matched asymptotic expansion method.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Though various experimental observations and numerical simulations explicitly suggest the significant effect of the convection on the interface microstructure formation, theoretical investigations of the morphological evolution of interface during crystallization in the stirred melt and solution are still very limited due to the complicated effects of convection. [2,[8][9][10][11][12][13][14][15][16][17] Hence, there is a strong need for the common analytical method to predict the experimentally observed particle morphologies developed under different flow conditions. A feasible way is to model the growth of spherical particles in the complex flow of the stirred liquid as a singularly perturbed free boundary problem and find its asymptotic solution by using the matched asymptotic expansion method.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, [19] we used perturbation series to obtain the solutions of temperature field and solute field under far-field flow. In our another paper, [20] the influence of a three-dimensional (3D) shear flow on morphological stability of a globular crystal interface was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[15] We found that the shear flow around the crystal can enhance the stability of the spherical interface. In another paper, [16] we used a perturbation series to obtain the solutions of the temperature and the solute fields.…”
Section: Introductionmentioning
confidence: 99%